An In-Depth Analysis of CdTe Thin-Film Deposition on Ultra-Thin Glass Substrates via Close-Spaced Sublimation (CSS) - Amin N.; Karim M.R.; Alothman Z.A. (MDPI, 2023)
This study evaluated the impact of the deposition pressure on the formation of cadmium telluride (CdTe) thin films on ultra-thin (100 m) Schott glass substrate at high temperature (T > 450?C) by Close-Spaced Sublimation (CSS) technique. CdTe thin films were grown under the pressure range of 1 Torr to 200 Torr to explore the impact of deposition pressure on CdTe thin-film properties. The microstructural, compositional and optoelectrical characteristics were examined. X-ray Diffraction (XRD) analysis revealed the cubic phase crystallite CdTe films with (111) preferential orientation. Scanning Electron Microscopy (SEM) demonstrated that the CdTe morphology and grain size could be regulated via the deposition pressure, whereby maximum grain growth was detected at low pressure (15 Torr). The thickness of CdTe films was reduced from 6 m to 1.5 m with the rise in deposition pressure. Moreover, the optical direct energy gap was derived in the range of 1.651.69 eV for the pressure value of 200 Torr to 1 Torr. Carrier density and resistivity were found to be in the order of 1013 cm?3 and 104 ? cm, respectively. The experimental results suggest that the pressure range of 15 Torr may be ideal for CSS-grown CdTe films on flexible ultra-thin glass (UTG) substrates. 2022 by the authors. Licensee MDPI, Basel, Switzerland.